Efeitos da obesidade no sistema calicreína-cininas: estudo dos receptores B1 e B2 de cininas em tecido adiposo humano e murino - Hilzendeger, Aline Mourão [UNIFESP] (2006)
Objectives: To study the effect of obesity on the kallikrein-kinin system through the expression of receptors B1 and B2 on humans and mice, and alterations in the synthesis and functionality of the receptor in murine tissues. Methods: white human adipose tissue and different kinds of mice tissues were collected. RNA was extracted and the kinin receptors expression analyzed through a real-time polymerase chain reaction. Tissues and organs such as stomach and aorta were used for protein extraction and physiological studies. By Western Blotting, receptor quantitation was studied. Stomach fungus and abdominal aorta were used to register isometric contractions to determine the potency and effectiveness of the agonists on obese and control mice. Increasing accumulating doses of bradykinin and des-Arg9-bradykinin, B2 and B1 receptors agonists respectively, were applied. Results: In the real-time PCR experiments, the gene expression of the B1 and B2 receptors were altered in some tissues of the animals deficient for leptin, when compared to the control. In the white adipose tissue, aorta, liver, hypothalamus and stomach, the B1 receptor expression was increased, but in cardiac tissues and brown adipose tissue, it was decreased. The expression of B2 receptor was decreased in white adipose tissue and hypothalamus. In the other studied tissues, no changes was detected in the B2 receptor expression. In humans, these receptors were altered in obese individuals. The study was performed in human adipose tissue from two different regions of depots, visceral and subcutaneous. There was a tendency of different expression in the same tissue, but from different areas. In tissues from obese mice the response to the B2 and B1 agonists, bradykinin and des-Arg9-bradykinin, respectively, had a decreasing tendency. A significant decrease was observed in stomach fundus in response to the BK agonist. Such effects can be due to the increased weight and its consequences, such as chronic inflammation or diabetes type II, which is a pathology directly related to obesity. Conclusion: expression and functional analysis show that obesity affects kinin receptors in many different mouse tissues as well as in humans.